Pengaruh metode latihan dan koordinasi mata tangan terhadap ketepatan drive pada ekstrakurikuler bulutangkis - Zulhendri Zulhendri; Pamuji Sukoco (Universitas Negeri Yogyakarta, 2021)
Penelitian ini bertujuan untuk mengetahui: (1) perbedaan pengaruh metode latihan drill tetap dan drill kombinasi (strokes) terhadap ketepatan pukulan drive; (2) perbedaan pengaruh koordinasi mata tangan tinggi dan koordinasi mata tangan rendah terhadap ketepatan pukulan drive; dan (3) Interaksi antara metode latihan dan koordinasi mata tangan terhadap ketepatan pukulan drive. Metode penelitian eksperimen faktorial 2 x 2. Populasi berjumlah 37 siswa. Sampel berjumlah 20 siswa. Instrumen koordinasi mata tangan menggunakan tes lempar tangkap bola tenis ketepatan pukulan drive menggunakan wall volley test. Teknik analisis data ANOVA dua jalur α = 0,05. Hasil menunjukkan: (1) ada perbedaan pengaruh metode latihan drill tetap dan drill kombinasi (strokes) terhadap ketepatan pukulan drive, drill tetap lebih baik daripada drill kombinasi (strokes); (2) ada perbedaan pengaruh koordinasi mata tangan tinggi dan rendah terhadap ketepatan pukulan drive, koordinasi mata tangan tinggi lebih baik daripada rendah; dan (3) ada interaksi antara metode latihan drill tetap dan drill kombinasi (strokes) dan koordinasi mata tangan tinggi dan rendah terhadap ketepatan pukulan drive. The effects of exercise and coordination of precision eye-hand drive in extracurricular badminton Abstract: This study aims to reveal: (1) differences in the influence of training methods drill fixed and drill combination (strokes) on the accuracy of punch drive; (2) differences in the effect of hand-eye coordination high and hand-eye coordination lower accuracy of the punch drives; and (3) the interaction between the practice and coordination hand-eye of the accuracy of punch drive. The method of this research was an experiment with factorial 2 x 2. The population was 37 students. The samples of this research were 20 students. The instrument to measure the use of hand-eye coordination catching tennis ball throwing punches accuracy-test drive using the wall volley. The data analysis technique was two ways ANOVA α = 0.05. The results of the research show that: (1) there are differences in the influence of training methods remain drill and drill combination (strokes) on the accuracy of punch drive, still better than the drill combination (strokes); (2) there is a significant difference of students that have the effect of hand-eye coordination high and low of the accuracy of punch drive, high hand-eye coordination is better than low; and (3) there was an interaction between training methods remain drill and drill combination (strokes) and hand-eye coordination high and low of the accuracy of punch drive.